Double station observation of Draconid meteor outburst from two moving aircraft. (1st December 2015) - Koten, Pavel; Vaubaillon, Jeremie; Margonis, Anastasios; Tóth, Juraj; Ďuriš, František; McAulliffe, Jonathan; Oberst, Jürgen
Abstract: A Draconid meteor shower outburst was observed from the boards of two scientific aircraft on 8 October 2011. In this paper we report the results of this double station experiment. The beginning and terminal heights are similar to other Draconid observations and confirm the fragile nature of the meteoroids. From the distribution function of terminal heights, a critical mass was found to be about 3.5 g. A behaviour of the terminal heights changes at this point. Light curves of Draconid meteors show great variability with a maximum of the F -number distribution around 0.35, which also confirms fragility of the material. Observed radiants of the meteors are in agreement with the theoretical model. Although encounters with two different filaments were predicted, it is impossible to distinguish between them from the radiants as well as the orbital data. Despite the complications with the data processing the airborne mission shows that such double station experiment is possible and provides valuable insight into meteor structure and dynamics.